Asymmetric synthesis of chiral heterobenzylic amines via visible-light-induced enantioselective C(sp3)-H alkylation - Yumei Huo; Beibei Chen; Xiaoyu Ren; Chao Wang; Rupeng Qi; Zhaoqing Xu (Green Synthesis and Catalysis)
The chiral heterobenzylic amines, such as α-alkyl substituted chiral oxadiazole methylamine skeletons are widely present in pesticides and pharmaceuticals, due to their unique biological activities. The enantioselective C(sp3)-H alkylation of heterobenzylic amines is an important strategy for the synthesis of α-alkylate chiral heterobenzylic amines. Herein, we disclose the first example of photoinduced and Cu-catalyzed enantioselective decarboxylative C(sp3)-H alkylation of oxadiazole methylamines.